Effectiveness of AEPS®-3 Intervention on Toddlers with Risk for Autism - K S Minu, K S Minu; Tiwari, Rahul (Journal of Neonatal Surgery, 2025)
This study evaluated the effectiveness of AEPS®-3 intervention in children under three years at risk for Autism Spectrum Disorder (ASD) across developmental domains- fine and gross motor, adaptive, cognitive and social behaviour and social communication. It also examined overall developmental outcomes and their association with demographic factors. The intervention involved parent-child sessions lasting four hours daily, six days a week, with home activities on the seventh day. The goal was to train parents in individualized strategies to support holistic child development. Seventy children identified as at risk for ASD were randomized into intervention and routine care groups, stratified by age and baseline characteristics. Standardized tools assessed outcomes every three months over ten months. All participants met M-CHAT-RTM criteria for ASD risk. Both groups received routine care, with no dropouts during intervention period. The intervention group showed significant improvements in fine and gross motor, adaptive skills, cognitive abilities, social communication, and social behaviour compared to the control group, as measured by AEPS®-3 total scores. AEPS®-3 intervention effectively enhanced early developmental skills in at-risk children. Significant gains highlight the importance of parent-centred strategies. Further studies with larger samples are recommended to confirm these findings and assess long-term impact.